Mitigating coercive parenting through home visitations: The impacts of a parenting program targeted at vulnerable communities in Jamaica - Francesco De Simone; Camila Mejia; José Martinez-Carrasco; Santiago M. Perez-Vincent; Harold Villalba (Inter-American Development Bank (IDB), 2022)
Family violence is a critical development challenge in low- and middle-income countries (LMICs), carrying high health, social, and economic costs and increasing the risk of perpetuating the cycle of violence across generations. Parenting programs have improved parenting practices in high-income countries. However, evidence for LMICs is sparse. This study evaluates an intervention to reduce coercive parenting implemented by the Ministry of National Security of Jamaica, which targeted caregivers of children aged 6 to 15 in vulnerable communities in the country. Treated caregivers were visited by a parental trainer for six months and invited to three sessions of a group training workshop during that period. We conducted a randomized controlled trial (RCT) to evaluate the intervention's impact. Using data from a follow-up survey completed six months after the intervention, we find robust evidence of reduced coercive parenting practices among treated caregivers compared to the control group. The improvement is due to a reduction in the reported likelihood of caregivers yelling and beating their children for misbehaving. The effect is greater for caregivers with higher pre-intervention levels of coercive parenting. The results provide evidence that parenting interventions can effectively reduce coercive parenting among caregivers of school-aged children in highly violent middle-income settings.
Keywords: J12; J13; 330; parenting; family violence; home visiting; randomizedcontrolled trial; Jamaica; PAFAS; Alabama ParentingQuestionnaire